Review Pelaksanaan Pengawasan Dinas Lingkungan Hidup Kabupaten Karawang Terhadap Pengelolaan Limbah Bahan Berbahaya dan Beracun oleh Kegiatan Industri - Alfy Nur Auliya Zahra; Ikhwanussafa Sadidan; Aziz Kemal Fauzie (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2024)
The Karawang Regency Government has a target to make Karawang Regency an industrial city. Based on open Jabar 2021 data, there are 1,608 industries in Karawang Regency, which has many negative impacts on the environment. Many industrial production processes use hazardous and toxic materials. The number of industries in Karawang Regency will increase the amount of hazardous and toxic waste that will be produced. Therefore, the supervision of industries is assigned to the Environmental Agency of Karawang Regency. This study aims to determine the supervisory function carried out by the Environmental Agency of Karawang Regency in the management of hazardous and toxic waste in industrial activities in Karawang Regency. The method used is by conducting direct observations and interviews at Environmental Agency of Karawang Regency with a span of 4 months. Based on the results of the research that has been carried out, Environmental Agency of Karawang Regency has carried out supervision of hazardous and toxic waste management properly and is in accordance with applicable laws and regulations, namely Law Number 32 of 2009. Supervision priority is given to industries that have potential violations, locations vulnerable to pollution, and high-risk activities. This effort aims to protect the environment, public health and sustainable natural resources. Supervision is conducted directly and indirectly. The management of hazardous and toxic waste has covered all aspects starting from the environmental documents to the hazardous and toxic waste management